The future of global financial services - Grosse, Robert E. (Malden, MA : Blackwell Publishing, 2004)
The book focuses on the changes that we will face in the near future, such as greater use of the internet for banking transactions and the increasing globalization of financial services. It considers changing conditions in key financial center around the world and points to the probable disappearance of the insurance sector as a separate industry. It describes the strategies of major financial services firms and the likelihood that it would be viable in the future.
Introduction -- The globalization of financial services -- The virtualization of financial services -- Government regulation : the second key factor underlying industry structure -- The financial landscape : organizations and allfinanz banking (the status quo) -- Competitive strategies of international financial institutions -- Competitiveness of commercial banks from key countries (or, Why are the US banks ahead?) -- Responding to the challenge of the new economy -- Why insurance won't survive -- Investment banking at the crossroads -- Financial instruments and financial structures -- The generation of long-term investment to support long-term bond and stock market growth -- International financial centers -- Surviving the twenty-first century.
Includes bibliographical references and index.
nmn 11/06/13
Loans
Keywords: Financial institutions, International; Financial services industry